Walkability, Transit Access, and Traffic Exposure for Low-Income Residents With Subsidized Housing - Houston, Douglas (American Public Health Association, 2013)
Objectives. We assessed the spatial distribution of subsidized housing units provided through 2 federally supported, low-income housing programs in Orange County, California, in relation to neighborhood walkability, transit access, and traffic exposure. Methods. We used data from multiple sources to examine land-use and health-related built environment factors near housing subsidized through the Housing Choice Voucher Program and the Low Income Housing Tax Credit (LIHTC) program, and to determine these patterns’ associations with traffic exposure. Results. Subsidized projects or units in walkable, poorer neighborhoods were associated with lower traffic exposure; higher traffic exposure was associated with more transit service, a Hispanic majority, and mixed-use areas. Voucher units are more likely than LIHTC projects to be located in high-traffic areas. Conclusions. Housing program design may affect the location of subsidized units, resulting in differential traffic exposure for households by program type. Further research is needed to better understand the relationships among subsidized housing locations, characteristics of the built environment, and health concerns such as traffic exposure, as well as which populations are most affected by these relationships.